2008
DOI: 10.4088/jcp.v69n0208
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Magnetic Stimulation in the Treatment of Major Depressive Disorder

Abstract: Background: Transcranial magnetic stimulation (TMS) has demonstrated efficacy in the treatment of major depressive disorder; however, prior studies have provided only partial safety information. We examined the acute efficacy of TMS in a randomized sham-controlled trial, under openlabel conditions, and its durability of benefit. Method: Aggregate safety data were obtained from a comprehensive clinical development program examining the use of TMS in the treatment of major depressive disorder. There were 3 separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(24 citation statements)
references
References 44 publications
1
20
0
3
Order By: Relevance
“…By noninvasively activating target cortical regions, TMS allows investigators to selectively study brain function in a simplified and relatively safe manner (Figiel et al, 1998; Klein et al, 1999). In the last few decades it has received considerable interest as a therapeutic tool in a variety of neurological disorders, stemming from its favorable spatial selectivity over ECT, noninvasive nature, and generally tolerable side effects (Figiel et al, 1998; Klein et al, 1999; Janicak et al, 2008). As a result, TMS is now used as an FDA-approved treatment option for refractory MDD.…”
Section: Alternative Therapies For Refractory Major Depressive Disordersmentioning
confidence: 99%
“…By noninvasively activating target cortical regions, TMS allows investigators to selectively study brain function in a simplified and relatively safe manner (Figiel et al, 1998; Klein et al, 1999). In the last few decades it has received considerable interest as a therapeutic tool in a variety of neurological disorders, stemming from its favorable spatial selectivity over ECT, noninvasive nature, and generally tolerable side effects (Figiel et al, 1998; Klein et al, 1999; Janicak et al, 2008). As a result, TMS is now used as an FDA-approved treatment option for refractory MDD.…”
Section: Alternative Therapies For Refractory Major Depressive Disordersmentioning
confidence: 99%
“…Several randomized, sham-controlled trials designated to investigate the antidepressant efficacy of rTMS also reported interesting findings regarding the effects of rTMS on cognitive performance [12,23,24,25,26,27,28,29,30,31,32,33,34]. However, given the limited availability of neurocognitive measures and the open nature of most available studies, to what extent rTMS may be really beneficial on neurocognitive performance is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we cannot exclude similar rTMS-induced cognitive dysfunctions as the one observed in our patient might have passed unnoticed. Indeed, some of the side effects of rTMS, such as agitation, hypomania, or mixed depressive episode, share core symptoms with a frontal lobe syndrome, and thus could easily be misdiagnosed (7, 8, 14, 15). Interestingly, all neurologic symptoms observed resolved shortly after the discontinuation of LF-rTMS and sertraline, without the use of specific therapeutics such as mood stabilizers.…”
Section: Discussionmentioning
confidence: 99%